Proyeksi Permintaan Listrik di Pulau Kalimantan dengan Mempertimbangkan Rencana Pembangunan Ibu Kota Nusantara (IKN) - Nuryanti; Elok S. Amitayani; Citra Candranurani; Nurlaila; Ewitha Nurulhuda; Yohanes Dwi Anggoro; Suparman (Prosiding Seminar Nasional Teknoka, 2023)
This study develops a model for forecasting electricity demand in the Kalimantan Island by considering the plan to build the IKN. Projections based on regression analysis are carried out for the West Kalimantan, Central & South Kalimantan and East & North Kalimantan region, while for the IKN the projection was based on the assumption of electricity consumption per capita. Variables that greatly influence the electricity demand based on the data analysis are GRDP, GRDP per capita, number of customers and electricity tariff. The projection result shows that the electricity demand in the Kalimantan Island with the construction of IKN area will increase from 12,542.20 GWh in 2022 to 147,639.96 GWh in 2060. In terms of the percentage of electricity sold per sector, there has been a significant decrease trend in the Household sector and a significant increase trend in the Industrial and Business sector.